Surface wind estimate from satellite pictures of sunglint - GOKHALE, M. N. (MAUSAM, 1971)
Satellite pictures of sunglint show a promise of providing a means of estimating wind over sea areas. A calm to light wind may give comparatively small but bright glint; whereas a stronger wind, generating waves may cause a diffuse reflection of sunlight and hence a diffused wider glint.